PENGARUH PEMBERIAN MOTIVASI, REWARD, DAN PUNISHMENT TERHADAP KINERJA GURU DI SEKOLAH MENENGAH ATAS TARUNA TUNAS BANGSA - Muhamat Husni; Yunita Sari; Yetty Okatrina (Bisnis-Net, 2026)
The Indonesian education sector continues to adapt to the challenges of the 21st century, where the quality of the learning process is of paramount importance. Teachers, as the driving force behind education, play a central role in achieving these objectives. Optimal teacher performance is not determined solely by academic competence, but is also significantly influenced by non-technical factors, particularly those of a motivational nature. In the context of human resource management in schools, the three main variables that are often the focus and align with the provisions of the regulations are motivation, rewards, and punishments. The research method employed in this study is a quantitative descriptive approach, with a sample size of 40 respondents comprising all teachers at Taruna Tunas Bangsa Senior High School, using SPSS version 25 for data analysis. The results indicate that the test of the Motivation variable (X1) against Teacher Performance (Y) yielded a significance value of 0.000 < 0.05. For the variable Reward (X2) on Teacher Performance (Y), a significance value of 0.001 < 0.05 was obtained. For the variable Punishment (X2) on Teacher Performance (Y), a significance value of 0.040 < 0.05 was obtained. The results of the simultaneous test of all parameters indicate that the F-value is 0.000 < 0.05. This means it can be concluded that there is a significant influence of the independent variables, both partially and simultaneously, on Teacher Performance (Y). Based on the calculations, the R-squared value was found to be 0.896. This R² value indicates that 89.6% of the variation in Teacher Performance (Y) can be explained by the variables Motivation (X1), Reward (X2), and Punishment (X3), whilst the remaining 10.4% is attributable to other variables not examined in this study.